Planning of erosti communications on the basis of building standards in the planning and construction of the city - M.H. Bobokalonov (Research Parks Publishing LLC, 2020)
In this article, the error of determining the location of points on the basis of building standards in the planning and construction of the city in the implementation plan of erosti communications and the norm of the distance between erosti communication networks are explained in detail.